2001
DOI: 10.1111/1468-2389.00163
|View full text |Cite
|
Sign up to set email alerts
|

Personality Predictors of Citizenship Performance

Abstract: This article briefly introduces the criterion construct, citizenship performance, describes how this construct is different from task performance and presents a recently derived 3-dimension model of the domain. Evidence is then reviewed for links between personality constructs and citizenship performance. An update of the Organ and Ryan (1995) meta-analysis of personality-organizational citizenship behavior relationships suggests slightly higher correlations than those found in the meta-analysis and also indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
335
2
18

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(375 citation statements)
references
References 51 publications
9
335
2
18
Order By: Relevance
“…Borman, Penner, Allen, and Motowidlo (2001) define citizenship performance as behaviors that contribute positively to the work place environment and enhance workers' task performance. The importance of these behaviors has been demonstrated by a number of studies that found a relationship between citizenship behaviors and productivity (e.g., Podsakoff, Ahearne, & MacKenzie, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Borman, Penner, Allen, and Motowidlo (2001) define citizenship performance as behaviors that contribute positively to the work place environment and enhance workers' task performance. The importance of these behaviors has been demonstrated by a number of studies that found a relationship between citizenship behaviors and productivity (e.g., Podsakoff, Ahearne, & MacKenzie, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a meta-analysis, Ng and Feldman (2008) evaluated the relationship between age and ten dimensions of job performance on the basis of 380 empirical studies. They suggest that the reason for mixed findings is to be traced to the fact that previous studies have focused rather narrowly on core task activities and neglected the activities that affect the environment in which core tasks take place, such as "organizational citizenship behavior" (Borman, Penner, Allen, and Motowidlo 2001;LePine, Erez, and Johnson 2002). The literature shows that the relationship between age and productivity is difficult to measure on the basis of empirical data.…”
Section: Relationship Age-productivity Between Facts and Stereotypesmentioning
confidence: 99%
“…Borman, Penner, Allen, & Motowidlo, 2001;Motowidlo, Borman, & Schmit, 1997). Table 1 displays the input parameter data used for the predictor and criterion mean subgroup differences, for the predictor validities and intercorrelations, as well as for the correlation between the two criterion dimensions.…”
Section: Selection Scenario and Parameter Datamentioning
confidence: 99%